2023
DOI: 10.1021/acs.jpclett.3c02242
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Properties of Zn2V(1–x)NbxN3 Alloys to Model Novel Materials for Light-Emitting Diodes

Ana-Maria Stratulat,
Christian Tantardini,
Maryam Azizi
et al.

Abstract: We propose the Zn2V(1–x)Nb x N3 alloy as a new promising material for optoelectronic applications, in particular for light-emitting diodes (LEDs). We perform accurate electronic-structure calculations of the alloy for several concentrations x using density-functional theory with meta-GGA exchange–correlation functional TB09. The band gap is found to vary between 2.2 and 2.9 eV with varying V/Nb concentration. This range is suitable for developing bright LEDs with tunable band gap as potential replacements for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 65 publications
1
5
0
Order By: Relevance
“…The obtained lattice constants of the primitive unit cell of bulk Zn 2 VN 3 are a = 5.61 Å, b = 9.59 Å and c = 5.29 Å; of bulk Zn 2 NbN 3 are a = 5.79 Å, b = 9.88 Å and c = 5.42 Å; and of bulk Zn 2 TaN 3 are a = 5.79 Å, b = 9.90 Å and c = 5.44 Å, respectively. The results are match well with the available theoretical and experimental results for bulk Zn 2 VN 3 and Zn 2 NbN 3 42,45,67,68.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…The obtained lattice constants of the primitive unit cell of bulk Zn 2 VN 3 are a = 5.61 Å, b = 9.59 Å and c = 5.29 Å; of bulk Zn 2 NbN 3 are a = 5.79 Å, b = 9.88 Å and c = 5.42 Å; and of bulk Zn 2 TaN 3 are a = 5.79 Å, b = 9.90 Å and c = 5.44 Å, respectively. The results are match well with the available theoretical and experimental results for bulk Zn 2 VN 3 and Zn 2 NbN 3 42,45,67,68.…”
supporting
confidence: 89%
“…The results are match well with the available theoretical and experimental results for bulk Zn 2 VN 3 and Zn 2 NbN 3 . 42,45,67,68…”
Section: Resultsmentioning
confidence: 99%
“…The results obtained for the lattice constants are consistent with previous works. 20,21 The band structure plots of the Zn 2 (V, Nb, Ta)N 3 monolayers obtained using the GGA PBE and HSE06 approaches are shown in Fig. 1(d)-(f).…”
Section: Methodsmentioning
confidence: 99%
“…19 Another group of potentially stable Zn 2 V (1-x) Nb x N 3 ternary nitride compounds has been theoretically tested; within studied concentrations, 0 r x r 1, the Zn 2 V 0.5 Nb 0.5 N 3 compound turned out to be the most stable structure. 20 Very recently, following the strategy of aforementioned works, a new family of stable 2D materials, Zn 2 (V, Nb, Ta)N 3 monolayers, has been predicted. 21,22 All above-mentioned ternary nitrides, including 2D samples, hold high promise for application in optoelectronics and are, therefore, of interest for in-depth study.…”
Section: Introductionmentioning
confidence: 99%
“…A ITO/TiZnN 2 /Si photodetector has been developed generating a photocurrent with a low light intensity and insensitive to humidity . It has also been shown that Zn 2 V (1– x ) Nb x N 3 alloys possess comparably small bowing parameter that is beneficial for materials used in light-emitting diodes …”
mentioning
confidence: 99%